The Inhibition Effect of Graphene Oxide Nanosheets on the Development of Streptococcus mutans Biofilms. (30th March 2017) - He, Jianliang; Zhu, Xiaodan; Qi, Zhengnan; Wang, Lihua; Aldalbahi, Ali; Shi, Jiye; Song, Shiping; Fan, Chunhai; Lv, Min; Tang, Zisheng
Abstract : Bacterial biofilms play a critical role in dental pathogenic mechanisms due to their ability to tolerate many traditional antibacterial agents. Thus, it is crucial to find effective methods to inhibit the occurrence and development of biofilms. Recently, graphene oxide (GO) nanosheets have become a promising antibacterial nanomaterial for use in various applications. This study focuses on the effect of GO nanosheets on the development of Streptococcus mutans biofilms. It is found that GO nanosheets are highly effective at inhibiting the formation of bacterial biofilms at concentrations ranging from low to high in early development stages. After GO treatment, the ratio of living cells in the biofilm decreases significantly, and the biofilm structure is destroyed. In contrast, GO has a minimal effect on mature biofilms. Abstract : The anti‐biofilm property of graphene oxide (GO) nanosheets is described. GO nanosheets can effectively inhibit biofilm formation at a broad range of concentrations during the early stages of bacterial biofilm formation. Biofilms treated by GO nanosheets display disintegrated structures, more inactive bacteria, and less extracellular polymeric substances. However, in the case of mature biofilms, GO has no effect on them.